Lumbar Puncture for Diagnosis of Idiopathic Intracranial Hypertension in Typical Patients. Issue 3 (September 2021) - Margolis, Mathew S.; DeBusk, Adam A.; Moster, Mark L.; Falardeau, Julie M.; Eggenberger, Eric R.; Sergott, Robert C.; Van Stavern, Gregory P.
Abstract : Background: Patients with typical features of pseudotumor cerebri syndrome (PTCS) must undergo lumbar puncture (LP) to demonstrate elevated opening pressure and cerebrospinal fluid (CSF) analysis to rule out alternative diagnoses. As LP may be associated with significant morbidity, this study aims to determine its necessity in diagnosing typical PTCS. Methods: Retrospective chart review at 3 university-based neuro-ophthalmology practices included women aged 18–45 years with body mass index >25, papilledema, negative neuroimaging, and who met criteria for PTCS or probable PTCS. Results: One hundred fifty-six patients were enrolled. Seven (4.5%) had clinically insignificant CSF abnormalities. No diagnoses or management changed based on LP/CSF results. Conclusion: LP may not be routinely required in the initial evaluation of typical patients with PTCS evaluated by experienced clinicians We caution, however, that further prospective study is required to determine potential risks and benefits of LP as a tool in the diagnosis of IIH before recommending general practice changes.